PENGARUH JUMLAH DANA PIHAK KETIGA, SUKU BUNGA KREDIT DAN NON PERFORMING LOAN TERHADAP PENYALURAN KREDIT PERBANKAN DI PROVINSI KALIMANTAN BARAT - B01111113, Eva Handayani (Jurnal Pembangunan dan Pemerataan, 2016)
ABSTRACTBank is a financial institution that serves the financial intermediaries. Banksaccept deposits from the public and channel them back to the community in the formof credit. Credit disbursement allow investment, distribution, and consumption ofgoods and services.The title of this study was the influence of the amount of third party fund(DPK), Interest Rates and Non Performing Loan (NPL) Against Credit Banking inWest Kalimantan Province. This study aims to determine how much influence thevariable amount of third party fund (DPK) to the bank credit in the province of WestKalimantan in 2005-2014, to know the effect of variable interest rate loans to thebank credit in West Kalimantan Province, and to determine how much influence NonPerforming Loan (NPL) terhadapa bank credit in the province of West Kalimantan.This study used quantitative descriptive method using multiple linear regressionmodel, as well as statistical analysis tools that test of determination (R2), F test and ttest to test the hypothesis whether the amount of third party funds (DPK), loaninterest rates, and non-performing loan (NPL) to bank credit.These results indicate that the amount of third party funds (DPK) positiveeffect of 1.194676 and significant, lending rates were affected positively by1580,176 and significant, while the NPL variable positive effect of 362.8483 and notsignificant to the bank credit in West Kalimantan. The coefficient of determination(R2) of 0.986831, which means the amount of influence exerted by a variablenumber of third party funds (DPK), loan interest rates, and Non Performing Loan(NPL) in West Kalimantan by 98%, while the remaining 2% are affected by other.Keywords: Banking Credit, Third Party Fund (DPK), Interest Rate Credit, AndNon Performing Loan (NPL).